Compliance to recall visits by patients with periodontitis - Is the practitioner responsible? - Fenol Angel; Mathew Simi (Wolters Kluwer Medknow Publications, 2010)
Context: Compliance to recall visit is directly related to the medium and long-term success of active periodontal therapy. Aims: To determine the percentage of patients who were compliant to recall visits by the practitioner and to find out the reasons for noncompliance by noncompliant patients. Settings and Design: Cross-sectional study was carried out in the Department of Periodontology, Amrita School of Dentistry. The study participants were former patients of the Department of Periodontology. Patients and Methods: A total of 216 patients were selected for the study - 116 males and 100 females. They were divided according to their socioeconomic status - professionals and nonprofessionals. Nonprofessionals were divided into those who had completed high school education and those who had not. They were followed up to find out how many were compliant to recall visits and the reasons for noncompliance by noncompliant patients. Statistical Analysis: The data was entered into SPSS version 11.5. Descriptive statistics were used. The frequencies of responses were calculated. Result: Of the total study population, 48.1% was compliant, of which 58.6% and 37.6% of males and females were compliant, respectively. In terms of percentage, 60.6% of professionals, 52.4% of those who had completed high school education and 31.3% of those who had not completed high school education were compliant. Conclusion: Compliance to recall visits by the periodontitis patients depends largely on the practitioner. Inadequate motivation by the practitioner and inadequate education in general are responsible for noncompliance to periodontal treatment.